Hot pursuit [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel, 2015)
Stone Barrington travels to Wichita to take possession of his long-awaited Citation M2, and is pleasantly surprised to find that the delivery pilot is a gorgeous woman who's soon moving to New York and is available for a closer acquaintance. Meanwhile, Stone is extended an invitation to a secret and private club, open to only the most exclusive membership.